2019
DOI: 10.4103/jfmpc.jfmpc_175_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of obstructive sleep apnea in metabolic syndrome

Abstract: Background: Metabolic syndrome has become one of the most important public health problems with a growing prevalence in both developed and developing countries. Obesity is a major risk factor for obstructive sleep apnea (OSA), which is associated with significant cardiorespiratory morbidity. Aims: The aims of this study were to find out the prevalence of OSA in patients with metabolic syndrome and to highlight the importance of assessment of OSA in these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…We should also emphasize that in addition to OSA, other disorders such as asthma, chronic obstructive pulmonary disease (COPD), interstitial lung disease, idipatic pulmonary fibrosis, and restrictive lung disease characteristically exhibit diurnal oscillations in oxygenation, and intermittent hypoxia is most likely to manifest during the sleep period, thereby potentially expanding the scope of our findings to many other relevant medical conditions. Of note, decreased insulin sensitivity has been reported in healthy volunteers, lean mice, and cultured adipocytes exposed to IH [72] , [73] , [74] . IH also leads to other vWAT changes such as gene expression modifications, alteration in lipoprotein clearance pathways, and vascular rarefaction [ 8 , 42 , 75 ], all of which play a central role in metabolic regulation and emergence of IR [ 8 , 9 , 41 , 43 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We should also emphasize that in addition to OSA, other disorders such as asthma, chronic obstructive pulmonary disease (COPD), interstitial lung disease, idipatic pulmonary fibrosis, and restrictive lung disease characteristically exhibit diurnal oscillations in oxygenation, and intermittent hypoxia is most likely to manifest during the sleep period, thereby potentially expanding the scope of our findings to many other relevant medical conditions. Of note, decreased insulin sensitivity has been reported in healthy volunteers, lean mice, and cultured adipocytes exposed to IH [72] , [73] , [74] . IH also leads to other vWAT changes such as gene expression modifications, alteration in lipoprotein clearance pathways, and vascular rarefaction [ 8 , 42 , 75 ], all of which play a central role in metabolic regulation and emergence of IR [ 8 , 9 , 41 , 43 ].…”
Section: Discussionmentioning
confidence: 94%
“…Our findings showing increases in IR and in vWAT M1 macrophages in mice exposed to IH along with improvements by PA, indicate that the vWAT may play a central role in metabolic regulation, and that chronic-low grade inflammation in vWAT is a key process in the emergence of IR [43] . Furthermore, clinical reports in untreated OSA patients have shown progressive worsening of IR, and the emergence of the metabolic syndrome with OSA severity, independent of obesity [70] , [71] , [72] , [73] . Indeed, obesity is one of the major risk factors for the occurrence of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome in Indian subcontinent has shown an increasing trend with a wide range of prevalence (11-40%). 12,18 'Syndrome Z' terminology was coined by Wilcox et al, to describe clinical condition with a combination of metabolic syndrome (Syndrome X) and OSA. 12,19 Untreated and severe grades of OSA lead to endocrine hormonal imbalances due to increased The present study was conducted at a tertiary care teaching hospital at Pune, Maharashtra.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria were considered for the study. 11,12 Patients aged ≥ 18 years, of either sex, who were diagnosed to be suffering from metabolic syndrome as per 'the 2005 International Diabetes Federation (IDF) criteria for metabolic syndrome' and who gave informed consent, were included in this study. According to the 2005 IDF criteria, metabolic syndrome is diagnosed in a patient having:…”
Section: International Diabetes Federationmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) can be a partial or complete narrowing of the pharyngeal airway [7]. Obesity has been a risk factor for OSA as patients have enlargement of soft tissue structures within and around the airway causing substantial pharyngeal airway narrowing [8]. Blankfield et al reported a significant association between idiopathic edema and OSA, particularly in women (P = 0.02) [9].…”
Section: Discussionmentioning
confidence: 99%